P6 The outcomes of maze surgery in achd patients. (2nd March 2016) - Carpenter, A; Khan, N; Stickley, J; Thorne, S; Hudsmith, L; Bowater, S; Clift, P
Abstract : Introduction: The percentage of patients falling under the category of adult congenital heart disease (ACHD) is increasing, with over 80% of those born with congenital heart disease surviving to adulthood. Whilst advances in surgery and interventional catheterisation are responsible for this, they can also contribute to the development of arrhythmias, alongside other causes including haemodynamic instability and electrical disturbances secondary to the defect. Should further cardiac surgery be planned, a concomitant Maze procedure is one way to assist in the management of this. The Queen Elizabeth Hospital, Birmingham is one centre offering the maze procedure. It is therefore important to audit the outcomes of surgery at this centre in comparison to previously published literature. Method: Data was collected from 67 patients with adult congenital heart disease who underwent a concomitant Cox MAZE procedure at the Queen Elizabeth Hospital from 2001 to 2015. 3 patients were excluded from the analysis due to incomplete data. A retrospective search was conducted to gather information on patient demographics, surgical history, pre and post-operative arrhythmias, use of anti-arrhythmic medication, occurrence of stroke and mortality.Early post-operative death was classified as any death within 30 days post-surgery, or during the same hospital stay. Recurrence of arrhythmia was defined as any documented atrial fibrillation (AF) or flutter after 3 months of surgery. Results: All patients had a concomitant procedure, the most common was an ASD closure (41.8%) and 56.7% underwent 3 or more procedures. The mean age at the time of the Cox MAZE procedure was 44.8, including 36 females (53.7%) and 31 males (46.3%). Pre-operative cardiac rhythm included atrial flutter (22.4%), atrial fibrillation (73.1%) and 3 which weren't documented (4.5%). Pre-operative AF was paroxysmal in 32, persistent in 6 and long standing persistent in 11 patients. There were two early post-operative deaths (3.0%). 12 month follow up was available for 64 patients (95.5%). At 12 months follow up, 79.7% had no recurrence of arrhythmias (n = 51), of which 39.1% (n = 25) were free from both arrhythmias and anti-arrhythmic medication. There was 1 death in the first 12 months (1.54%). Long term follow up following the first 12 months was available for 52 patients (77.6%), with a mean length of follow up of 4.1 years (Range 1.1–14.4). At long term follow up, 80.4% were free from arrhythmias (n = 41) and 43.1% were free from both arrhythmias and anti-arrhythmic medication and there were a further 3 deaths (5.9%). Conclusion: Whilst the results of this audit do not match that of the published data, it is important to note there is limited published literature using adult congenital heart disease patients to compare to. Further research is needed to assess the outcomes of maze procedures in those undergoing multiple concomitant procedures, as seen in the population of patients used here. Nevertheless, this audit demonstrates a high success rate of concomitant maze operations at the Queen Elizabeth Hospital.